Greenhouse Nematode Management, Florida Greenhouse Vegetable Production Handbook - Vol 3 - Joseph W. Noling; Jimmy R. Rich (EDIS)
HS1158, an 8-page illustrated fact sheet by J. W. Noling and J. R. Rich, is part of the July 2009 revision of SP-48 Florida Greenhouse Vegetable Production Handbook, volume 3. It describes the practices and considerations for nematode management in greenhouse production. Published by the UF Department of Horticultural Sciences, July 2009.